5x+3y=-9
-2x+y=8
The first step is the trickery (and quite frankly, hardest to explain) part. You need to multiply one equation by a number that will create one variable to be the negative version of the other...(Confusing, right? Don't worry, I'll show you)
We are going to solve for X first.
We will multiply the second equation by -3
5x+3y=-9
-3(-2x+y)=(-3)8
Now simplify:
5x+3y= -9
6x-3y= -24
Now combine the two equations (add them together)
11x= -33
Divide by 11
X=-3
Now plug X in to one of the first equations:
5(-3)+3y= -9
-15+3y =-9
3Y= 6
Y= 2
So your final answer is:
x= -3
Y= 2
Hope this helps!
Answer:
4
Step-by-step explanation:
Answer:
ok
Step-by-step explanation:
Answer:
approx. 25.13
Step-by-step explanation:
C= 2πr
radius is half diameter
Answer:
is this your only question?